Variation in biochemistry test results between annual wellness visits in apparently healthy Golden Retrievers. (2nd February 2021) - Jeffery, Unity; Jeffery, Nick D.; Creevy, Kate E.; Page, Rod; Simpson, Melissa J.
Abstract: Background: Annual wellness testing is widely recommended for apparently healthy dogs, but there is little data to assist with distinguishing normal variation from clinically important changes. Objectives: To define variability in biochemistry analytes between annual wellness tests in healthy Golden Retrievers. Animals: Four hundred thirty‐four Golden Retrievers undergoing annual health assessments by their primary care veterinarians as part of a prospective cohort study. Methods: Changes in 23 biochemistry analytes were calculated between year 1 and year 2 health checks for 196 dogs classified as healthy for ≥3 consecutive years. Using a direct nonparametric method, annual change intervals were constructed to define normal variability. A validation cohort of 238 dogs without a diagnosis of systemic disease for ≥3 consecutive years were compared with the reference and annual change intervals, and the proportions of dogs outside annual change intervals and a population‐based reference interval were compared by using a McNemar test. Results: Annual change intervals were calculated based on 190 dogs after outlier removal. For all 23 analytes, >90% of dogs in the validation cohort were within the annual change interval. There were no significant differences in the classification by reference versus annual change intervals. Conclusions and Clinical Importance: The annual change intervals met performance requirements for classification of dogs that did not develop systemic disease in the year following wellness testing as normal.